Experimental evaluation of graphene oxide/TiO2-alumina nanocomposite membranes performance for hydrogen separation. (4th March 2020) - Zeynali, R.; Ghasemzadeh, K.; Iulianelli, A.; Basile, A.
Abstract: In recent years, graphene oxide membranes showed interesting performances in terms of high permeating flux and perm-selectivity in several applications of gas separation because of their inherent properties combined to a low energy consumption. In this paper, a graphene oxide layer is coated on modified TiO2 -alumina tubular substrate in order to prepare graphene oxide nanocomposite membranes useful for hydrogen separation. Nanocomposite graphene oxide membrane samples were obtained by using vacuum deep coating method, depositing the graphene oxide solution as single layers on TiO2 -alumina substrate. Temperature and pressure variations were evaluated to achieve high H2 permeance, high H2 /CO2 selectivity and membrane performance stability during the experimental tests. Furthermore, it was found that the temperature increase causes a perm-selectivity (H2 /N2 and H2 /CO2 ) decrease, while the transmembrane pressure increase involves a general improvement of the perm-selectivity. Highlights: Graphene oxide membranes were obtained by using vacuum deep coating method. The α-alumina surface support was modified by controlling the particles size in TiO2 -Boehmit sol. The presence of large pores in graphene oxide thin film structure allowed a permeance increase at higher temperature.